Perancangan SITANI Sebagai Media Informasi Bagi Petani - Eko Harry Pratisto; Arif Budi Waluyo (Universitas Sebelas Maret, 2017)
Agriculture is one source of livelihood of people in Surakarta. However, there are some problems that occur in agriculture, such as: the shortage of agricultural goods, the difficulty of obtaining workshop activities information, and difficulty to sell crops at harvest periode for the arragement price from middlemen.SITANI application is develop using waterfall method and built using Java programming language with tool Android Studio. The design includes table of functional requirements, use case diagram, ERD, activity diagrams, and interface design. Application testing is done using quistionnaire.The results of this research is the creation of android-based application with modules SITANI advertsement, workshop activities information, and ordering goods.